Proposal of production model based on lean and continuous improvement to improve the productivity in smes of baking: an empirical investigation in Peru - Zamalloa Menacho, Alanis Alessandra (2023)
In Peru, the food industry represents 16.52% of GDP and bread is one of the foods that generated the highest consumption; however, despite the demand, bakery SMEs have a negative performance. Poor process management and methods are used affecting its pro- ductivity. Faced with this problem, SMEs in Europe are using the Lean Manufacturing methodology to optimize their processes. That is why this article proposes as a contribution the Lean-Deming Model, which includes tools such as Poka Yoke, Work Standardiza- tion, 5S and Deming Cycle. To validate this contribution, the model was developed in a bakery SME in Lima, Peru in its "pan frances" production line. A simulation of the improvements in the Arena Software was carried out, with which positive results were obtained. Searching tools times decreased by 10.34% and labor productivity improved by 23.91%, thus improving overall process productivity.